2003
DOI: 10.1021/bm0300251
|View full text |Cite
|
Sign up to set email alerts
|

Static Water Structure Detected by Heat Capacity Measurements on Aqueous Solutions of a Triple-Helical Polysaccharide Schizophyllan

Abstract: Heat capacity measurements were made on aqueous solutions of a triple-helical polysaccharide schizophyllan by precision adiabatic calorimetry over a wide range of concentrations 30.45-90.93 wt % at temperatures between 5 and 315 K. The heat capacity curves obtained were divided into four groups depending on the weight fraction of schizophyllan w regions I-IV. In region I, triple-helices with the sheath of bound water, structured water, and loosely structured water forming layers around the helix core are embed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 47 publications
2
29
0
1
Order By: Relevance
“…A cross-sectional view of the triple helix of β-glucan in water showed that it has four water boundaries, rendering it difficult to dissolve in water. The approximate diameters of the innermost core and outermost shell of the helix are 1.68 and 2.79 nm, respectively (Yoshiba et al ., 2003). X-ray crystallographic studies showed that the triple helix formation of schizophyllan has a diameter of 2.6 nm and a 1.8-nm pitch.…”
Section: Structure-activity Relationship Of β-Glucansmentioning
confidence: 99%
“…A cross-sectional view of the triple helix of β-glucan in water showed that it has four water boundaries, rendering it difficult to dissolve in water. The approximate diameters of the innermost core and outermost shell of the helix are 1.68 and 2.79 nm, respectively (Yoshiba et al ., 2003). X-ray crystallographic studies showed that the triple helix formation of schizophyllan has a diameter of 2.6 nm and a 1.8-nm pitch.…”
Section: Structure-activity Relationship Of β-Glucansmentioning
confidence: 99%
“…This due to the concentration dependence of the transition, as will be discussed in a separate publication. 47 Table II summarizes the solution concentrations and used parameter values. Figure 8 presents a schematic view of the molecular mechanism behind this transition.…”
Section: Order-disorder Transitionmentioning
confidence: 99%
“…Here C P EX is positive at all ‡ It has been found that the number of unfreezable water molecules is almost constant between w ϭ 0.0448 Ϫ 0.718. 47 This finding along with the very small difference in C p between the annealed and quenched samples is taken to show that schizophyllan is molecularly dispersed even in the frozen state. temperatures and contains the order-disorder transition peak around 290 K. It is suggested that C P EX mainly originates from the interaction between schizophyllan and water, so-called solvation, and so forth, but no detailed molecular mechanism is as yet proposed.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…3)-b-D-glucans, but neither possesses antitumor properties because both have single helical structures. Yet schizophylalan, pachymaran and carboxymethylpachymaran have marked antitumor activity (Ooi 2009;Yoshiba et al 2003;Chihara et al 1970bChihara et al , 1987Hamuro et al 1971). All have triple helical structures.…”
Section: Resultsmentioning
confidence: 99%